Women and the Net: The Stories - Garcia, Moises S. (Kasarinlan: Philippine Journal of Third World Studies; Vol 16 No 1 (2001): Gender and Sexuality, 2008)
A book review of Pi Villanueva's "Women and the Net: The Stories"